Anti-Infective Activity of Momordica charantia Extract with Molecular Docking of Its Triterpenoid Glycosides - Mohammed Aldholmi; Rizwan Ahmad; Mohammad Habeeb Shaikh; Ayad Mohammed Salem; Maher Alqurashi; Mansour Alturki (MDPI AG, 2024)
Momordica charantia, commonly known as bitter melon, is a fruiting plant that has been used for several diseases including infectious diseases. In this study, we report the antibacterial, antifungal, and antiviral activity of different bitter melon fruit parts originating from India and Saudi Arabia. The in vitro experiments are supported by the molecular docking of karavilosides to verify their role in the bioactivity. The antimicrobial assays revealed activity against Candida albicans, Escherichia coli, and Staphylococcus aureus. The extracts exhibited the potent inhibition of HIV-I reverse transcriptase, with an IC50 of 0.125 mg/mL observed for the pith extract originating from Saudi Arabia and the standard drug doxorubicin. The molecular docking of karavilosides exhibited a significant affinity to reverse transcriptase comparable to Rilpivirine and higher than that of doxorubicin. These outcomes encourage the precious bioactive components of the seed and pith of the Saudi bitter melon fruits to be further studied for isolation and structure elucidation.